International Migration of Skilled Workers with Endogenous Policies - Slobodan Djajic; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the interaction between the optimal immigration policy of a host country and education policy of a source country in a model of international migration of skilled workers. Acquisition of human capital is driven by the academic and career opportunities at home and abroad. Greater opportunities to migrate are found to increase the source country's net stock of human capital only under very stringent conditions concerning the shape of the utility function and of the production function for human capital, the country's emigration rate, and the international wage differential. We use the model to examine the effects of technological improvements in the educational sector, changes in the academic curricula in the source country, and attitudes to immigration in the host country. Of key interest are the implications for the optimal spending on education in the source country and the optimal immigration quota of the host country.
Keywords: F22; J24; O15; 330; migration of skilled workers; immigration policy; education policy